IMPROVEMENT OF THE NATIONAL MECHANISM FOR RESPONDING TO CASES OF DOMESTIC VIOLENCE AND GENDER-BASED VIOLENCE AGAINST UKRAINIAN CITIZENS ABROAD - ЛЕГЕНЬКИЙ, Микола; ЛЕВЧЕНКО, Катерина; ЛЕГЕНЬКА, Марина; ДУНЕБАБІНА, Ольга (Київський національний університет імені Тараса Шевченка, 2025)
Background. Social problems concerning ensuring human rights in Ukraine in general and protecting citizens from domestic and gender-based violence in particular, which have become especially urgent as a result of full-scale armed aggression of the Russian Federation, are highlighted. With reference to international legal acts, the need for special legal and social protection of internally displaced persons, in particular those who have left Ukraine, is substantiated. Methods. The study is based on the method of a comprehensive systematic study of the socio-political and regulatory situation that has developed in Ukraine and the countries of temporary stay of its citizens due to the need to protect against largescale armed aggression by the Russian Federation and the need for further deployment of measures for social and legal protection of this category of citizens. Results. The study on prevention and counteraction to domestic violence among refugees in different countries has been analyzed and summarized. A number of factors have been identified that cause the aggravation of the situation among internally displaced persons, which, in turn, requires strengthening of human rights work with this particular category of persons on the part of the subjects of prevention and counteraction to domestic violence. Particular attention is paid to the situation regarding social protection of Ukrainian citizens, who, in order to protect them from the results of full-scale armed aggression of the Russian Federation, were forced to leave Ukraine. The thesis on the need to strengthen the social and legal protection of the abovementioned category of persons from domestic and gender-based violence is substantiated. Conclusions. It was emphasized that this situation limits the opportunities for Ukrainian citizens affected by domestic violence to use mechanisms available in the host country for protection and access to justice. The reasons for this restriction include the lack of proper legal knowledge, discrimination by the authorities of the host state, ignorance of the language, threats from the offender, etc. At the same time, with reference to international and national legislation, the principles of extending Ukraine's obligations to protect the human rights of its citizens abroad are highlighted. It is proved that the solution to this problem is possible by expanding the list of entities that take measures in the field of prevention and counteraction to domestic violence and gender-based violence by including foreign diplomatic missions of Ukraine in such a list. It was emphasized that such measures require legislative regulation, namely the introduction of appropriate amendments and additions to the laws of Ukraine "On Prevention and Counteraction to Domestic Violence" and "On Ensuring Equal Rights and Opportunities for Women and Men". The positive consequences of these legislative innovations are predicted.

Вступ. Висвітлено суспільні проблеми стосовно забезпечення в Україні прав людини загалом і захисту громадян від домашнього та ґендерно зумовленого насильства зокрема, які набули особливої актуальності внаслідок повномасштабної збройної агресії російської федерації. З посиланням на міжнародні нормативно-правові акти обґрунтована необхідність особливого правового й соціального захисту вимушених переселенців, зокрема тих, які виїхали за межі України. Методи. Дослідження базується на методиці комплексного системного вивчення суспільно-політичної і нормативно-правової ситуації, що склалася в Україні та країнах тимчасового перебування її громадян, у зв'язку з необхідністю захисту від широкомасштабної збройної агресії російської федерації і подальшим розгортанням заходів щодо соціально-правового захисту цієї категорії громадян. Результати. Проаналізовано й узагальнено дослідження щодо запобігання і протидії домашньому насильству серед біженців у різних країнах. Виявлено низку факторів, які спричиняють загострення ситуації саме в середовищі вимушених переселенців, що, у свою чергу, вимагає посилення правозахисної роботи із цією категорією осіб із боку суб'єктів запобігання та протидії домашньому насильству. Особливу увагу приділено ситуації щодо соціального захисту громадян України, які з метою убезпечення від результатів повномасштабної збройної агресії російської федерації були змушені виїхати за межі своєї країни. Обґрунтовано тезу щодо необхідності посилення соціального й правового захисту вищезазначеної категорії осіб від домашнього та ґендерно зумовленого насильства. Висновки. Підкреслено, що вказана ситуація пов'язана з обмеженням можливостей громадян України, які постраждали від домашнього насильства, у частині використання наявних у країні перебування механізмів забезпечення захисту й доступу до правосуддя осіб. До причин такого обмеження належать: відсутність належних правових знань; дискримінація з боку органів влади держави перебування; незнання мови; погрози з боку кривдника тощо. При цьому з посиланням на міжнародне й національне законодавство висвітлено засади поширення зобов'язань України із захисту прав людини на її громадян, які перебувають за кордоном. Доведено, що розв'язання вказаної проблеми можливе шляхом розширення переліку суб'єктів, що здійснюють заходи у сфері запобігання та протидії домашньому насильству й насильству за ознакою статі шляхом включення до такого переліку закордонних дипломатичних установ України. Підкреслено, що подібні заходи потребують законодавчого врегулювання, а саме внесення відповідних змін і доповнень до законів України "Про запобігання та протидію домашньому насильству" і "Про забезпечення рівних прав та можливостей жінок і чоловіків". Прогнозовано позитивні наслідки зазначених законотворчих новацій.
УДОСКОНАЛЕННЯ НАЦІОНАЛЬНОГО МЕХАНІЗМУ РЕАГУВАННЯ НА ВИПАДКИ ДОМАШНЬОГО НАСИЛЬСТВА ТА НАСИЛЬСТВА ЗА ОЗНАКОЮ СТАТІ СТОСОВНО ГРОМАДЯН УКРАЇНИ ЗА КОРДОНОМ
Keywords: Council of Europe Convention on preventing and combating violence against women and domestic violence; domestic violence; gender-based violence; Russia's armed aggression against Ukraine; Ukrainian citizens abroad; assistance to victims of violence; Конвенція Ради Європи із запобігання насильства стосовно жінок і домашнього насильства та боротьби із цими явищами; домашнє насильство; ґендерно зумовлене насильство; збройна агресія російської федерації проти України; українські громадяни за кордоном; допомога постраждалим